AGING EFFECTS ON BRAIN METABOLISM AND ITS RESPONSE TO MENTAL ACTIVITY. (16th November 2018) - Vlassenko, A; Couture, L; Durbin, T; Raichle, M; Goyal, M
Abstract: In young adults, task performance and sensory stimulation induces an increase in total glucose metabolism (CMRGlc) and cerebral blood flow (CBF) but only slight change in oxygen metabolism (CMRO2) in the stimulated brain region. Aging is associated with specific topographic changes in the resting state brain metabolism, especially in aerobic glycolysis (AG), which decreases across the lifespan. AG has a role in multiple metabolic pathways associated with neuroprotection, biosynthesis, synaptic plasticity and learning. In this study, we evaluated effects of aging on changes in AG, CMRGlc, CMRO2 and CBF in response to mental activity. Positron emission tomography (PET) studies using inhalation of 15O-CO and 15O-O2, and injection of 15O-water, and 18F-fluorodeoxyglucose (FDG) were performed in 29 healthy cognitively normal participants (10 young and 19 older adults) at rest and during performance of the word stem completion task. AG, CMRGlc, CMRO2 and CBF were calculated for brain regions defined using FreeSurfer software and partial volume correction. Topographic analysis of this PET imaging data demonstrated that in young adults, the task condition evoked both increases (visual cortex) and decreases (anterior cingulate, precuneus) in AG, CBF and CMRGlc, whereas minimal changes were seen in CMRO2. These findings were not significantly different in the older participants compared to the younger adults. The dissociation between aging related differences in resting brain AG and their absence in task-induced AG suggest that the drivers of resting brain AG might differ from those causing a rise in AG during brain stimulation.